Mastery of Arabic Grammar (Qawaʿid) Among Grade XI Students of Madrasah Aliyah Negeri 1 Majene - Fauziah Jufri; Syahruddin Usman; Azizul Hakim (Abjadia : International Journal of Education, 2026)
Mastery of qawāʿid (Arabic grammar) is a fundamental aspect of Arabic language learning, particularly in mubtada’-khabar and fiʻil-fāʻil, which form the core structure of nominal and verbal sentences. However, in practice, not all students are able to master these two aspects optimally. This study aims to describe the mastery level of mubtada’-khabar and fiʻil-fāʻil among Grade XI students at MAN 1 Majene. This research employed a quantitative approach with a descriptive design. The sample consisted of 57 students selected using purposive sampling. Data were collected through a validated written test administered to 57 Grade XI students and analyzed using descriptive statistics and a One Sample t-test. The results showed that the average mastery score for mubtada’-khabar was 61.05 and for fiʻil-fāʻil was 64.74, both falling below the minimum mastery criterion (KKM) of 75. Although fiʻil-fāʻil was generally better mastered than mubtada’-khabar, the distribution of mastery was not uniform across students. In conclusion, mastery of both aspects needs to be improved through more contextual, interactive, and varied learning, supported by gradual practice and the use of media that can visualize sentence structures effectively.